A Combined RNA Preservation and Extraction Protocol for Gene Expression Studies in Cacao Beans - De Wever, Jocelyn; Tulkens, Dieter; Verwaeren, Jan; Everaert, Helena; Rottiers, Hayley; Dewettinck, Koen; Lefever, Steve; Messens, Kathy (Frontiers in Plant Science, 2020)
Despite the high economic importance of cacao beans, few RNA-based studies have been conducted on this plant material and hence no optimal RNA-extraction has been reported. Moreover, extraction of high-quality RNA from recalcitrant cacao bean tissue has shown many difficulties and requires optimization. Furthermore, cacao beans are mostly found at remote and under-resourced locations, which pressures the outsourcing of such analysis and thereby demands RNA-stable preservation and transportation of cacao beans. This study aims to select an appropriate RNA extraction and preservation/transportation method for cacao beans. For this purpose, three sample homogenization and five extraction protocols on cacao beans were compared. In addition, 13 preservation conditions – differing in tissue crushing degree, preservation method, duration and temperature – were compared and evaluated. A comparative analysis revealed that CTAB-based homogenization and extraction outcompeted all tested commercial protocols in RNA yield and integrity, respectively. Preservation at -80 °C affected RNA quality the least, whereas freeze-drying was most suitable for transportation at room temperature for maximum one week. The cacao bean RNA obtained from the selected methods were compatible for downstream applications. The results of this study will facilitate on-field sampling and transportation of genetically sensitive cacao material prior to cacao bean transcriptomic studies. In addition, valuable insights on sample homogenization, extraction, preservation and transportation have been provided, which is of interest to every plant geneticist.